Excavations at Tuleilat Qasr Mousa Hamid - Verduci, J.A. (Buried History: The Journal of the Australian Institute of Archaeology, 2016)
Tuleilat Qasr Mousa Hamid, in southern Jordan, is believed to be the Iron Agesite of biblical Zoar. This paper reports on an excavation that was undertaken in January 2015. It is clear from finds that there was a significant agricultural and industrial settlement at the site in the Iron Age II period.